2019
DOI: 10.4283/jmag.2019.24.1.081
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Magnetic Field and Second-Order Slip Flow of Casson Liquid with Heat Transfer Subject to Suction/Injection and Convective Boundary Condition

Abstract: The present article is planned theoretically to throw light on non-Newtonian Casson liquid flow and heat transport analysis over an exponentially stretching sheet with second-order velocity slip condition. The analysis of magneto-hydrodynamic (MHD) is an important interdisciplinary field. One of the most imperative applications related to engineering problems is plasma confinement, liquid-metal cooling of nuclear reactors, and electromagnetic casting. The flow here is considered to be electrically conducting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The effect of β on f η ( ) [Color figure can be viewed at wileyonlinelibrary.com] effects within the channel due to the Hartmann number Ha. Profound findings 21,22 have revealed that the fluid velocity decreases while temperature increases for the higher values of Ha. Physically, the resistive force is the called Lorentz force strengthening when the magnetic field is applied normal to the surge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of β on f η ( ) [Color figure can be viewed at wileyonlinelibrary.com] effects within the channel due to the Hartmann number Ha. Profound findings 21,22 have revealed that the fluid velocity decreases while temperature increases for the higher values of Ha. Physically, the resistive force is the called Lorentz force strengthening when the magnetic field is applied normal to the surge.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the ion slip with Hall effects is analyzed by Bhatti et al 21 for the radiative Casson flow. In another analysis of Majeed et al, 22 the second-order slip flow of the Casson fluid with the heat transfer and suction-injection effects is considered. Zeeshan et al 23 provided the results of partial slip effects on the mixed convection of ferromagnetic fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Majeed et al (2018) investigated ferromagnetic impact with heat transfer on stretching sheet. Majeed et al (2019b) discoursed second-order slip impact on MHD incompressible flow over a stretchable surface with convective boundary surface. Dinarvand et al (2016) testified unsteady mixed convective stagnation point flow by using the Tiwari–Das model.…”
Section: Introductionmentioning
confidence: 99%
“…Tu and Deville [9] earlier show blood like the behaviour of Casson fluid and discussed pulsatile flow in arterial stenoses. More recently, Majeed et al [10] investigated the influence of higher-order wall slip of Casson fluid along with heat transfer and suction/injection. They also consider the uniform magnetic field and convective thermal boundary condition.…”
Section: Introductionmentioning
confidence: 99%